PROSEDUR PELAKSANAAN EVENT DI HOTEL SWISSBELL BALIKPAPAN SELAMA MASA PANDEMI COVID 19 - Ranti Rustika; Abdul Gafur; Tri Retno Nugroho, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2023)
The COVID-19 pandemic is still spreading in Balikpapan. This made the income of several hotels in Balikpapan decreased and even had to be closed because they could not expand their businesses. Several ways have been done by the hotel to stay afloat, including getting income from organizing some events. However, during the COVID-19 pandemic, the procedure for organizing events is not the same as before the pandemic. Several procedures must be carried out in organizing an Event, one of them is to apply the CHSE procedure. With the above problems, the researcher wanted to know how to apply the CHSE procedure in carrying out the Event at the Swissbell Hotel Balikpapan. The application of this CHSE is one of the standards that must be applied by every hotel during the COVID-19 pandemic in various fields. The purpose of this study was to find out the procedure for implementing the Event during the Covid 19 Pandemic in a hotel that took a case study at the Swissbell Hotel Balikpapan. The method used is a qualitative descriptive method with the analysis stages from reduction, display and conclusion. The results of this study are the implementation of CHSE in event activities at the Swissbell Balikpapan hotel has been carried out well, but there are several obstacles in its application, such as the lack of order for visitors to wear masks and room sterilization which causes additional time for employees to work.